Real-time operating system for autonomous drone control - Swarnika Bhardwaj (Innovative Research Thoughts, 2023)
Drones have become a transformative force across industries in the quickly changing world of autonomous technologies. Their applications are expanding, from precision agriculture to emergency response, thanks to developments in real-time operating systems. A key development is a "Real-time operating system for autonomous drone control" that reshapes the potential of unmanned aerial vehicles through the convergence of high-speed data processing, low-latency responsiveness, and complex control algorithms. Autonomous drones once imagined only in science fiction, are now a real possibility and are revolutionizing a wide range of industries. The integration of autonomous drones has created new opportunities for efficiency, safety, and scalability in a variety of fields, from agriculture and logistics to disaster relief and surveillance. The ability of a real-time operating system to process information with microsecond-level responsiveness is essential to the success of these initiatives because it enables drones to navigate dynamic environments, adapt to unexpected changes, and make quick decisions.